A Janus-Like Asylum: The City and the Institutional Confinement of the Mentally Ill in Victorian Ontario - Wright, David; Day, Shawn; Smith, Jessica; Flis, Nathan (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2008)
This paper examines several aspects of the complex relationship between the city and the Victorian lunatic asylum. The first part of the paper demonstrates that the urban-ness of the public mental hospital has been a point of some degree of ambiguity. Mental hospitals were Janus-like—looking forward to the emerging urban world and yet, at the same time, looking back to a romanticized, rustic past. The second part of the paper adopts a quantitative approach and reveals that, far from the receptacle of strictly urban dwellers, the mental hospitals received a remarkable number of mentally ill from rural regions of the province. This finding, derived from one of the largest database studies of mental hospital patients ever undertaken, revises an important and longstanding argument in the historiography of the North American mental hospital.